Narrative experiments : the discursive authority of science and technology - Ormiston, Gayle L., 1951- (University of Minnesota Press, 1989)
Narrative Experiments was first published in 1989. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. In Narrative Experiments, Gayle Ormiston and Ralph Sassower bring a refreshing perspective to the domains of inquiry we call ""science"" and ""technology, "" asserting that traditional definitions (like classical idealism and materialism) fail to suggest the rich and complex cultural/linguistic interplay occurring between them. This context is not merely a